2017
DOI: 10.1016/j.nrl.2016.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Calidad de vida relacionada con la salud en cuidadores de pacientes con enfermedad de Alzheimer

Abstract: HRQOL in caregivers of patients with Alzheimer's disease deteriorates over time and is poorer than that of the age- and sex-matched general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 30 publications
3
11
0
6
Order By: Relevance
“…Other findings reported in the present study are consistent with previous research; we also found that caregivers had a poorer HRQoL than non-caregivers [10][11][12]22,32,33] and experience more pain/discomfort and anger/hostility [37]. This may be due to their daily caring tasks, the functional disabilities of the patients, and the duties involved in patient supervision [38].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Other findings reported in the present study are consistent with previous research; we also found that caregivers had a poorer HRQoL than non-caregivers [10][11][12]22,32,33] and experience more pain/discomfort and anger/hostility [37]. This may be due to their daily caring tasks, the functional disabilities of the patients, and the duties involved in patient supervision [38].…”
Section: Discussionsupporting
confidence: 91%
“…In fact, the caregivers in our study spent more than twenty hours per week taking care of their patients, possibly giving the impression of permanent care. In particular, somatization episodes can be due to the ailments derived from physical problems such as back pain, pain in the knees, body pain or fatigue that have been reported in previous studies with caregivers of patients with AD [11,12,14,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, the exercise of the role of the caregiver leads to a wide variety of physical, psychological, social and financial difficulties [7,[12][13][14][15]. In this regard, the adverse effects on physical health and quality of life are diverse [16][17][18][19][20]. Informal caregivers show higher rates of hypertension and other cardiovascular-related disorders [21,22], as well as lower aerobic endurance [23] than non-caregivers.…”
Section: Introductionmentioning
confidence: 99%
“…Esta situación ha desencadenado que las asociaciones, fundaciones y la sociedad en general se preocupe y sensibilice cada vez más no sólo con las personas que padecen enfermedad de Alzheimer, sino también con aquellos familiares o cuidadores que ven alterada su vida diaria por dedicarles el tiempo y los cuidados que necesitan (Tabla 5.1). La sociedad está cada día más concienciada del estrés físico y emocional que genera la convivencia con una persona con demencia y sus cuidados, lo que se traduce en un mayor interés en proporcionar recursos y apoyos para este colectivo (Laserna et al, 1997), (Kotradyová, 2018), (Garzón-Maldonado et al, 2017), (Biurrun Unzué, 2001), (Cuesta, Patterson, Lemus, Williams, & Jiménez, 2017).…”
Section: Síntomas Y Factores De Riesgounclassified